2017
DOI: 10.1159/000478872
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1/GLP-1R Signaling in Regulation of Adipocyte Differentiation and Lipogenesis

Abstract: Key Words Liraglutide • 3T3-L1 preadipocytes • Adipogenesis • FASN AbstractBackground/Aims: The aim of this study was to determine the direct role of liraglutide (LG) in adipogenesis and lipid metabolism. Methods: Lipid accumulation was evaluated by oil red O staining, quantitative real-time PCR (qPCR) was performed to determine glucagon-like peptide 1 receptor (GLP-1R), fatty acid synthase (FASN) and adipose triglyceride lipase (ATGL) expression in 3T3-L1 preadipocytes, differentiated adipocytes and in adipos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 49 publications
0
47
0
Order By: Relevance
“…Patients with DM have multiple systemic risk factors that likely contribute together to the endothelial phenotype observed, including differences in lipid profile. Prior studies have shown that administration of GLP‐1 agonists has an impact on lipid homeostasis 72, 73, 74, 75. Liraglutide administration appears to have beneficial effects on plasma lipids and lipoproteins, including a reduction in total cholesterol, triglycerides, and low‐density lipoprotein cholesterol, and an increase in high‐density lipoprotein cholesterol 76, 77, 78.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with DM have multiple systemic risk factors that likely contribute together to the endothelial phenotype observed, including differences in lipid profile. Prior studies have shown that administration of GLP‐1 agonists has an impact on lipid homeostasis 72, 73, 74, 75. Liraglutide administration appears to have beneficial effects on plasma lipids and lipoproteins, including a reduction in total cholesterol, triglycerides, and low‐density lipoprotein cholesterol, and an increase in high‐density lipoprotein cholesterol 76, 77, 78.…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunction of adipocyte and adipose tissue may cause health problems such as human obesity and metabolic syndrome [2,3]. Additionally, adipose tissue deposition is highly related to meat quality and animal productivity in farm animals [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the key role played by GLP-1 in mediating lipid metabolism, much researches has aimed to understand the cellular and molecular mechanisms involved [18,19,40]. Fat accumulation in the liver is regarded as a key pathogenic factor of metabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…GLP-1 has unique abilities to modulate lipid metabolism by affecting lipid assimilation and transport, fat formation and decomposition, hepatic lipid metabolism and reverse cholesterol transport [17,18,19]. The apolipoprotein A-I gene, encoding the primary anti-atherogenic factor in high-density lipoprotein (HDL) particles, is increased in both GLP-1 and exendin-4-treated HepG2 cells, and this phenomenon is accompanied by similar changes in the expression of ABCA1 [20].…”
Section: Introductionmentioning
confidence: 99%